Effect of ionic strength on trivalent iron and lanthanum adsorption by TEMPO-oxidized nanofibrillated cellulose - Salla H. Venäläinen (Cleaner Engineering and Technology, 2023)
Charged biopolymers able to adsorb solubilized metal cations instead of precipitating them as inorganic waste provide a sustainable option for conventional lime treatment of acidic metal-bearing effluents. We investigated the adsorption of trivalent iron (Fe3+) and lanthanum (La3+) on anionic TEMPO (2,2,6,6-tetramethyl-piperidine-1-oxyl)-oxidized nanofibrillated cellulose (TONFC) from concentrated solutions at increasing ionic strengths (I). In the adsorption experiments, solutions containing 25–150 mM FeCl3 or LaCl3 as such (I0), or with I adjusted to 1 (I1) or 4 (I4) with NaCl, were treated with TONFC. Following filtration, the solutions were subjected to pH measurement and analysis for the TONFC-induced changes in Fe and La concentrations. The susceptibility of the retained metals to desorption was elucidated by back extraction. Adsorption of Fe3+ and La3+ significantly exceeded the negative charge density of TONFC, which led to positive overcharging of cellulose fibrils. The consequent Coulomb repulsion between the fibrils prevented their aggregation and enabled metal retention even under highly acidic conditions. At high I, Na + ions derived from the NaCl background were unable to compete with Fe3+ or La3+ for the sorption sites. Excess of Cl- ions, in turn, produced chloride complexes, particularly with Fe3+. They abated overcharging, which induced TONFC condensation and reduced Fe sorption within a critical concentration range. Above this range, Fe sorption recovered presumably due to partial redispersion of cellulose fibrils. Analogous condensation and redispersion of TONFC was not detected in the reaction with La3+. In conclusion, its overcharging tendency renders TONFC a superior agent for the treatment of highly concentrated metal-bearing effluents of very low pH. Successful utilization of the material as a water purification agent, however, requires understanding of the re-entrant behavior of TONFC with solutions of high I.